The controversial role of nutraceuticals vs. drugs in proliferative retinopathies - Rusciano, Dario; Bagnoli, Paola (Frontiers in Neuroscience, 2026)
Neovascular eye diseases, notably age-related macular degeneration and diabetic retinopathy, remain major causes of vision loss despite advances in pharmacological management. The proliferation of abnormal retinal blood vessels leads to the loss of retinal cells and progressive visual dysfunction. Anti-VEGF therapies have revolutionized treatment; however, their efficacy is incomplete, they require repeated administration, and resistance or suboptimal responses are not uncommon. These limitations have stimulated interest in additional therapeutic approaches, both inspired by preclinical research and aimed at improving the management of systemic conditions that contribute to neovascular pathologies. Beyond conventional pharmacology, nutraceuticals have attracted attention for their proposed mechanisms—enhancement of antioxidant defenses, modulation of inflammatory cascades, and potential interference with angiogenic signaling—which provide a molecular rationale for their application in ocular disease. This review critically examines the dual landscape of current pharmacological strategies and nutraceutical approaches, analyzing how the latter might enhance retinal resilience and vascular stability in the early stages of disease. The novelty of this work lies in juxtaposing the mechanistic underpinnings of nutraceuticals with the clinical shortcomings of anti-VEGF therapy, thereby identifying opportunities for integrative therapeutic perspectives. Nevertheless, nutraceuticals cannot replace pharmacological treatment in advanced disease; rather, they may offer incremental benefits in early-stage or high-risk patients, contingent upon timely preventive diagnosis. Until more robust clinical evidence and regulatory oversight are established, nutraceuticals should be regarded as adjunctive components within personalized care models—supporting, but not substituting for, established pharmacological interventions.